Analysis on Analytical Exposition Texts Written by 11th Grade Students from SMAN 1 Sungairaya - Mahardika, Surya; Yuliana, Yohanes Gatot Sutapa; Riyanti, Dwi (Celt: A Journal of Culture, English Language Teaching & Literature, 2025)
The purpose of this study is to describe the students' writing ability by analyzing the student's analytical exposition text through qualitative research. The research subjects in this study consist of 30 eleventh-grade students from SMAN 1 Sungai Raya. The researchers employ 6-traits of writing rubrics to examine the students’ works. The findings mainly focus on two pivotal aspects, which are the development of students' ideas and organization and their proficiency in students' written conventions. The analysis shows that the majority of the students are able to write a simple and clear main idea. The researcher found that most of the students use multiple details or reasons to support the main idea. They are capable of constructing the analytical exposition text, which elaborates ideas, supports, and details the language features and generic structure of the text, and the writing convention. Based on the analysis of conventions in students’ writing, the students demonstrate varied levels of competence in writing conventions, showing strengths in some areas like punctuation and grammar but facing challenges, particularly in spelling and specific aspects of capitalization. In conclusion, they have good basic writing skills but need practice and exposure to writing English.